2020
DOI: 10.1021/jacs.9b11370
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Electron-Doping Mechanism in Potassium-Intercalated Single-Walled Carbon Nanotubes

Abstract: Single-walled carbon nanotubes (SWCNTs) can be doped with potassium, similar to graphite, leading to intercalation compounds. These binary systems exhibit a clear metallic character. However, the entire picture of how electron doping (edoping) modifies the SWCNTs' vibrational spectra as a function of their diameter, chirality, and metallicity is still elusive. Herein, we present a detailed study of the intercalation and solid state reduction of metallic and semiconducting enriched HiPco ® SWCNTs. We performed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The RBM frequency is inversely proportional to the SWCNT’s diameter, obeying the relation ω RBM = α/ d + ω 0 , where α is the constant of proportionality between the RBM frequency and the SWCNT’s diameter and ω 0 is dependent on the SWCNT’s physicochemical environment. Using the DFT-calculated diameters d in Å from Table , we find that α ≈ 221.8 × 10 –7 and ω 0 ≈ 17.5 cm –1 give the best fit to the RBM frequencies of ref , as shown in Figure d. Such values are consistent with those previously reported for other SWCNT samples. , …”
Section: Resultsmentioning
confidence: 79%
“…The RBM frequency is inversely proportional to the SWCNT’s diameter, obeying the relation ω RBM = α/ d + ω 0 , where α is the constant of proportionality between the RBM frequency and the SWCNT’s diameter and ω 0 is dependent on the SWCNT’s physicochemical environment. Using the DFT-calculated diameters d in Å from Table , we find that α ≈ 221.8 × 10 –7 and ω 0 ≈ 17.5 cm –1 give the best fit to the RBM frequencies of ref , as shown in Figure d. Such values are consistent with those previously reported for other SWCNT samples. , …”
Section: Resultsmentioning
confidence: 79%
“…Herein, the IG/ID values of SWNTs and SWNTs/EDC are 11.7 and 4.2, respectively, demonstrating the presence of EDC. Additionally, the diameters of the SWNTs were calculated from the radial breathing modes (RBMs) ( Kröckel et al, 2020 ). In order to analyze Raman spectra, the formula ωRBM = A/d + B is used, where A = 234 cm −1 , B = 10 cm −1 , ωRBM is the radial breathing mode, and d is the diameter of the nanotube.…”
Section: Resultsmentioning
confidence: 99%
“…3 (b)). Previous advances have suggested that the electronical properties of quasi 1D structures such as single-walled carbon nanotubes 31 depend on their diameter and chirality. Similarly, we find that the band gap can be controlled by changing the chirality and size of the few-chain Te nanowires.…”
Section: Resultsmentioning
confidence: 99%